2018
DOI: 10.1007/s10533-018-0458-6
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum effects on marine phytoplankton: implications for a revised Iron Hypothesis (Iron–Aluminum Hypothesis)

Abstract: In contrast to substantial studies and established knowledge of aluminum (Al) effects 2 (mainly toxicity) on freshwater organisms and terrestrial plants, and even on human 3 health, only a few studies of Al effects on marine organisms have been reported, and our 4 understanding of the role of Al in marine biogeochemistry is limited. In this paper, we 5 the role of Al in the stimulation of phytoplankton growth and carbon sequestration in the 1 ocean depths. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 120 publications
(142 reference statements)
3
29
0
Order By: Relevance
“…Thus, effects on growth of marine algae caused by Al seem unlikely. The same conclusion was drawn by Zhou et al, who reviewed the aluminum toxicity to marine phytoplankton [17]. However, Gillmore et al showed that diatoms with higher silicon content in cell walls are more sensitive [33].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, effects on growth of marine algae caused by Al seem unlikely. The same conclusion was drawn by Zhou et al, who reviewed the aluminum toxicity to marine phytoplankton [17]. However, Gillmore et al showed that diatoms with higher silicon content in cell walls are more sensitive [33].…”
Section: Discussionsupporting
confidence: 65%
“…In this context, compared to invertebrates, fish have been proven to be particularly sensitive to Al exposition, in neutral to basic water a no effect concentration of 100 µg/l Al was reported for trouts. In contrast, marine studies on the ecotoxicological impact of galvanic anodes are scarce [17]. So far, very little attention has been paid to studying the toxicity and accumulation of Al in benthic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an upsurge of interest in the effects of Al on marine organisms in recent years. With reference to marine phytoplankton, recent studies have reported both the toxicity (Gillmore et al, 2016;Golding et al, 2015) and the beneficial effects of Al on marine phytoplankton growth (Liu et al, 2018;Zhou et al, 2018aZhou et al, , 2018bZhou et al, , 2016. However, little is known about the uptake kinetics and the intracellular fate of Al in marine phytoplankton, which are important if we are to understand the mechanisms responsible for the biological effects of Al.…”
Section: Introductionmentioning
confidence: 99%
“…3) analysis of the cultured C. meneghiniana , from which the Al species associated with the organic components of the Al-bearing lake diatoms were determined. Notably, the specific mechanisms, explaining why diatoms take up Al into their frustules and how Al is transported or distributed between the inorganic and organic components of diatoms are unknown and have never been explored 35 .
Fig. 5Al/Si atomic ratios of cultured diatoms and their frustules.
…”
Section: Resultsmentioning
confidence: 99%